Effects of maternal dietary olive oil on pathways involved in diabetic embryopathy - Higa, Romina Daniela (2014)
Maternal diabetes induces a pro-oxidant/pro-inflammatory intrauterine environment related to the induction of congenital anomalies. Peroxisome proliferator activated receptors (PPARs) are transcription factors that regulate antioxidant and anti-inflammatory pathways. We investigated whether maternal diets supplemented with olive oil, enriched in oleic acid, a PPAR agonist, can regulate the expression of PPAR system genes, levels of lipoperoxidation and activity of matrix metalloproteinases (MMPs) and their endogenous inhibitors (TIMPs) in embryos and decidua from diabetic rats. The embryos and decidua from diabetic rats showed reduced expression of PPARs and increased concentration of lipoperoxidation, MMPs and TIMPs, whereas the maternal treatments enriched in olive oil increased PPARδ in embryos and PPARγ and PPARγ-coactivator-1α expression in decidua, and increased TIMPs concentrations and decreased lipoperoxidation and MMPs activity in both tissues. Thus, maternal diets enriched in olive oil can regulate embryonic and decidual PPAR system genes expression and reduce the pro-oxidant/pro-inflammatory environment during rat early organogenesis.